2015
DOI: 10.5796/electrochemistry.83.810
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Na-insertion/Extraction Properties of Sn–P Anodes

Abstract: Thick-film electrodes of tin phosphides, Sn 4 P 3 and SnP 3 , were prepared using a mechanical alloying method followed by a gas-deposition method, and were evaluated as Na-ion battery anodes in an organic electrolyte and ionic liquid electrolytes. The Sn 4 P 3 electrode showed a better cycling performance in the organic electrolyte compared with the SnP 3 electrode and an Sn electrode. The performance of the Sn 4 P 3 electrode was further improved by using ionic liquid electrolytes because of a uniformly form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…In the subsequent cycles, a cathodic peak was observed at 0.4 V vs. Na + /Na and a cathodic current rise was observed at 0.2 V, which correspond to sodiation reactions of elemental P 26 and elemental Sn 25 , respectively. Summarizing the above, the reaction mechanism is illustrated in Figure 4 As several researchers have reported [20][21][22] , we confirmed that the electrode reaction occurs as follows: Sn4P3 phase forms Na15Sn4 and Na3P via its phase separation in the first sodiation, and elemental Sn and elemental P individually react with Na ions at different potential regions in the subsequent cycles. (Fig.S4), demonstrating that crystalline Sn4P3 phase changed to amorphous-like phase and/or nanocrystalline phase with several nanometers in size.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…In the subsequent cycles, a cathodic peak was observed at 0.4 V vs. Na + /Na and a cathodic current rise was observed at 0.2 V, which correspond to sodiation reactions of elemental P 26 and elemental Sn 25 , respectively. Summarizing the above, the reaction mechanism is illustrated in Figure 4 As several researchers have reported [20][21][22] , we confirmed that the electrode reaction occurs as follows: Sn4P3 phase forms Na15Sn4 and Na3P via its phase separation in the first sodiation, and elemental Sn and elemental P individually react with Na ions at different potential regions in the subsequent cycles. (Fig.S4), demonstrating that crystalline Sn4P3 phase changed to amorphous-like phase and/or nanocrystalline phase with several nanometers in size.…”
mentioning
confidence: 57%
“…For this problem, Yang et al 20 , Kim et al 21 , and the authors 22 have revealed that the Sn4P3 negative electrodes exhibited better cycling performances in conventional organic electrolytes than the P and Sn negative electrodes. The improvements in the performances are probably attributed to complementary effects of Sn and Na3P formed by sodiation of P: metallic Sn acts as a conducting pathway to activate the reversible sodiation of nonconductive Na3P phase, while the Na3P phase provides a shield matrix preventing Sn aggregation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Tin phosphide (Sn 4 P 3 ) is a promising anode in sodium ion batteries (SIBs), due to its high theoretical capacity of 1131 mA h g À1 and reasonably low redox potential (~0.3-0.6 V vs. Na/Na + ), as well as the low cost of both Sn and P. [1][2][3][4][5][6][7][8][9][10][11][12] However, phase pure Sn 4 P 3 suffers from poor cyclic stability, as commonly ascribed to a number of factors, including the volume expansion induced electrode pulverization and large stress that limits the Na dynamics, and the chemical instability in the electrode (e. g., solid electrolyte interphase (SEI), sodiated phases of NaÀP, and tin segregation during charging/discharging). [13][14][15][16] Introducing an appropriate second phase to form composite with Sn 4 P 3 would be an effective approach to improve the electrochemical performance of the electrode, if it can help to buffer the volume expansion and at the same time stabilize various species in the electrode.…”
Section: Introductionmentioning
confidence: 99%